2020
DOI: 10.1016/j.aop.2020.168124
|View full text |Cite
|
Sign up to set email alerts
|

Stability of gravastars with exterior regular black holes

Abstract: This paper examines the stability of thin-shell gravastars in the context of regular spacetimes (Bardeen and Bardeen-de Sitter black holes). We apply cut and paste approach to construct gravastars through the matching of interior non-singular de Sitter geometry with exterior regular black hole. This model contains three regions, i.e., interior, thin-shell and exterior. The interior and exterior regions are connected at thin-shell. We investigate physical viability of the developed model by the energy condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Rahaman et al [35] studied numerous viable features for gravastar structures in 3-dimensional spacetime with the contribution of charge. Sharif and Javed [36] investigated the stable configuration of gravastars by considering quintessence as well as regular black hole geometries in the interior and observed linear profiles of physical variables versus the thickness of the shell.…”
Section: Introductionmentioning
confidence: 99%
“…Rahaman et al [35] studied numerous viable features for gravastar structures in 3-dimensional spacetime with the contribution of charge. Sharif and Javed [36] investigated the stable configuration of gravastars by considering quintessence as well as regular black hole geometries in the interior and observed linear profiles of physical variables versus the thickness of the shell.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the developed structure follows the null energy condition and shows stable behavior for some suitable values of physical parameter near the expected event horizon. Recently, we have developed regular thin-shell gravastars in the background of Bardeen/Bardeen DS BHs as exterior manifolds through cut and paste method [16]. The stable configuration of the developed structure is explored through radial perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the developed structure follows the null energy condition and shows stable behavior for some suitable values of physical parameter near the expected event horizon. Recently, we have developed regular thin-shell gravastars in the background of Bardeen/Bardeen DS BHs as exterior manifolds through cut and paste method [13]. The stable configuration of the developed structure is explored through radial perturbation.…”
Section: Introductionmentioning
confidence: 99%